Authoring Future Identities: Latina Girls Reading and Writing the University. (3rd July 2019) - Flores, Tracey T.; Batista-Morales, Nathaly; Salmerón, Cori
Abstract : In this article, we describe the campus visit we organized for Latina girls (grades 6–12) that participated in Somos Escritoras/We Are Writers. Somos Escritoras is a creative space that invites Latina girls to explore their lives and examine their worlds through art, writing, and theater. We focus on the writing marathon we designed for our visit and share the ways this activity invited girls to read and write the campus, while re-imagining their stories and authoring their futures. Drawing on figured words, we discuss how a campus visit can support Latina girls in constructing identities as future college students and graduates.